Analisis Tinggi Gelombang Laut di Perairan Buton Selatan - Hasrifin, Hasrifin; Iskandar, Ahmad; Nanda Kharisma, Gaby; Kamur, Sudarwin (Mataram University, 2024)
Wave height information is very much needed by the people of South Buton, especially those who always use sea transportation, therefore this study aims to analyze the sea wave height in the waters of South Buton, using a quantitative descriptive method. The data collection technique is in the form of documentation. The data analysis technique used is a descriptive statistical analysis technique. Wave height information is very much needed by the community, especially in the shipping sector and fishermen in the waters of South Buton. The results of this study show that the wave height in South Buton varies greatly from January to December from 2019, 2020, and 2021. The months with great potential for high waves are January, February, April, and June with an average wave height of 1-3 meters with a wind speed of 4-15 knots. The lowest and moderate waves occur in March, May, July, August, September, October, November, and December. In these months, the average wave height reaches 0-2.5 meters with a wind speed of 6-15 knots.